2018
DOI: 10.1007/s11356-018-2839-8
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and histopathology as biomarkers for evaluation of the effects of paracetamol and propranolol in the neotropical fish species Phalloceros harpagos

Abstract: Pharmaceutical drugs in the aquatic environment can induce adverse effects on nontarget organisms. This study aimed to assess the short-term effects of sublethal concentrations of both paracetamol and propranolol on the fish Phalloceros harpagos, specifically light/dark preference, swimming patterns, skin pigmentation, histopathology, and liver glycogen levels. Fish were acutely exposed to sublethal concentrations of both paracetamol (0.008, 0.08, 0.8, 8, 80 mg L) and propranolol (0.0001, 0.001, 0.01, 0.1, 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 110 publications
1
12
0
Order By: Relevance
“…The decrease in lactate dehydrogenase activity observed in the present study may have occurred because the organism may have favored the use of the aerobic route for energy production , suggesting that the energy balance of aerobic processes was enough to supply the metabolism of the fish under study. This suggestion is supported by the study conducted by Matus et al (2018), who analyzed the behavior, tegumentary staining and glycogen reserves in the liver of P. harpagos during acute exposure to the same concentrations of paracetamol.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The decrease in lactate dehydrogenase activity observed in the present study may have occurred because the organism may have favored the use of the aerobic route for energy production , suggesting that the energy balance of aerobic processes was enough to supply the metabolism of the fish under study. This suggestion is supported by the study conducted by Matus et al (2018), who analyzed the behavior, tegumentary staining and glycogen reserves in the liver of P. harpagos during acute exposure to the same concentrations of paracetamol.…”
Section: Discussionmentioning
confidence: 62%
“…This species presents favorable features for its laboratory use, such as high sensitivity to environmental contaminants, availability and abundance in its habitat, easy capture and adaptation to laboratory conditions, being representative of the neotropical environment. These features turn it into a good candidate for ecotoxicological studies (COSTA et al, 2008;PEREIRA et al, 2018;MATUS et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Furtherly, it has now been established that the nervous control of chromatophores in teleosts is exerted by the sympathetic system ( 50 ) and NE, a neurotransmitter of the sympathetic fibers, is believed to be responsible for signal transmission and leads to pigment aggregation ( 23 , 42 , 52 – 59 ). In our present study, after being treated with NE, the black spots on the excised skin changed to blue color, demonstrating that the color of spots are regulated by sympathetic nerves, and the neurotransmitter NE plays an role in regulating malanophores aggregation to make spots appear blue.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports has shown that Acetaminophen can act as potential endocrine disruptor, induce oxidative stress, hepatotoxic, neurotoxic and disrupt physiological process in exposed aquatic organism; hindering the usual embryonic development, growth, behaviour and survival of Daino rerio and Clarias gariepinus larvae (David andPancharatna 2009, Erhunmwunse et al, 2021). Sublethal concentrations altered swimming behaviour, pigmentation and energy balance in Phalloceros harpagos (Matus et al, 2018). Sublethal concentrations induced endocrine disruption and altered the liver structure in male sh Rhamdia quelen (Guiloski et al, 2017); induced oxidative stress in Clarias gariepinus (Folarin et al, 2018;Yakubu et al, 2020).…”
mentioning
confidence: 99%